Photovoltaic analysis of the effects of PEDOT:PSS-additives hole selective contacts on the efficiency and lifetime performance of inverted organic solar cells - Savva, Achilleas; Georgiou, Efthymios; Papazoglou, Giannis; Chrusou, Alexandra; Kapnisis, Konstantinos; Choulis, Stelios A. (My University, 2015)
Solution processed inverted organic photovoltaics (OPVs) usually use (Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) PEDOT:PSS derivatives as hole selective contact. In this study the effect of different PEDOT:PSS formulations, Al4083, PH and PH500 in inverted structured OPVs is investigated. Through detailed device physics analysis PEDOT:PSS PH is proposed as most suitable hole selective contact for inverted OPVs device function. Furthermore, PEDOT:PSS PH hole selective contact is treated with 3 different wetting agents, Zonyl FS-300 fluorosurfactant (Zonyl), 2,5,8,11-tetramethyl-6-dodecyn-5,8-diol ethoxylate (Dynol) and Zonyl:Dynol mixture and the corresponding non-encapsulated inverted OPVs investigated under accelerated humidity lifetime conditions. The inverted OPVs incorporating PEDOT:PSS:Zonyl hole selective contact shown limitations on humidity lifetime performance due to the poorest adhesion properties of Zonyl-treated PEDOT:PSS PH compared with Dynol and Zonyl/Dynol mixture treaded PEDOT:PSS PH.
Keywords: Additives; Device performance; Hole selective contact; Inverted organic photovoltaics; PEDOT:PSS; Processing